SYNTHESIS, SPECTRAL ANALYSIS AND ANTIBACTERIAL EVALUATION OF 5-SUBSTITUTED-1,3,4- OXADIAZOL-2-YL 4-(4-METHYLPIPERIDIN-1-YLSULFONYL)BENZYL SULFIDES - Rehman, Aziz Ur; Ahtzaz, Samreen; Abbasi, Muhammad Athar; Siddiqui, Sabahat Zahra; Rasool, Shahid; Ahmad, Irshad (Journal of the Chilean Chemical Society, 2017)
Owing to valuable biological activities of 1,3,4-oxadiazole, sulfamoyl and piperidine functionalities, some new 1-(4-[(5-substituted-1,3,4-oxadiazol-2-yl) thio]methylbenzene sulfonyl)-4-methylpiperidine (6a-o) derivatives have been introduced. The target molecules were synthesized from different aralkyl/aryl carboxylic acids, 1a-o, through a series of steps. First the compounds, 1a-o, were converted to heterocyclic 1,3,4-oxadiazole nucleophiles, 4a-o. Second an electrophile as 1-(4-bromomethylbenzenesulfonyl)-4-methylpiperidine (5) was synthesized from 4-methylpiperidine. Finally the target compounds, 6a-o, were prepared by reacting 4a-o with 5 in DMF and LiH. The final compounds were structurally elucidated by spectral data of IR, 1H-NMR and EI-MS. All the compounds were screened for their antibacterial evaluation and found to exhibit valuable results.